Negragrion sagma gen.n. and sp.n. from South America with a morphological phylogeny of the New World Ischnurinae (Odonata: Zygoptera: Coenagrionidae) - Muzon, Javier (2020)
A new coenagrionid genus, Negragrion, is described for N. sagma sp.n. found in Argentina and Brazil (Holotype and allotype, pair in tandem. Argentina: Corrientes: Santo Tomé, arroyo Ita Cuá sobre RP 94, 28°26’48.30”S 56°00’33.11”W, 24.ii.2003, Muzón & Pessacq coll., MLP). The new genus is characterized by the shape of male cerci (decumbent from base; saddle-shaped; in lateral view with an acute apophysis directed dorsally located at 0.3 from base). The presence of a vulvar spine on S8 of females places this genus within Ischnurinae. A cladistics analysis using morphological data was carried out to determine its phylogenetic position. Negragrion gen.n. is recovered within the clade 4 as the sister group of the clade (Acanthallagma Acanthagrion (Oxyagrion, Fluminagrion)).